Bio-based films with improved water resistance derived from soy protein isolate and stearic acid via bioconjugation. (20th March 2019) - Ye, Qianqian; Han, Yufei; Zhang, Jizhi; Zhang, Wei; Xia, Changlei; Li, Jianzhang
Abstract: Consumed plastic packaging materials give rise to many severely negative environmental effects. As a coproduct from the soybean oil industry, soy protein isolate can be remanufactured into value-added products to replace plastics; however, the use of the soy protein isolate films developed to date has been hindered by their poor water resistance. In this work, stearic acid was applied to enhance the water resistance of the soy protein isolate films via the bioconjugation technique. The water resistance, water barrier properties, morphology, mechanical, thermal properties and mechanism of the modified films were evaluated. The successful grafting of stearic acid onto the protein via bioconjugation was confirmed by the attenuated total reflectance-Fourier transform infrared spectroscopy and X-ray diffraction measurements. As expected, stearic acid modification greatly improved the water resistance of the films. The addition of 10 wt% stearic acid contributed to a 35.3% (p < 0.05) water vapor permeability reduction, 35.8% (p < 0.05) moisture content reduction and 74.4% (p < 0.05) water absorption reduction relative to the unmodified film. Meanwhile, the water contact angle increased from 45.8° for the unmodified film to 104.6° for the modified film. Furthermore, the Young's modulus of the modified films increased, and their tensile strength and elongation at break decreased compared with those of the unmodified film. However, the decrease in the tensile strength of the obtained films was smaller than those of the physically modified soy protein isolate films. This research can help understand the effects of the chemical modification of fatty acids on soy protein isolate films, and the obtained films exhibit potential for utilization in the food packaging industry. Graphical abstract: Highlights: The films were prepared by bio-based materials. The water resistance of films was enhanced by bio-based and hydrophobic stearic acid. via The issue of interfacial compatibility between stearic acid and SPI protein were solved via bioconjugation. The water resistance, surface hydrophobicity, and water vapor barrier property were enhanced after modification.